2009
DOI: 10.1136/jnnp.2009.185363
|View full text |Cite
|
Sign up to set email alerts
|

Early profiles of clinical evolution after intravenous thrombolysis in an unselected stroke population

Abstract: Early clinical profiles of evolution in thrombolysed patients vary considerably. Even with CI, it is critical to maintain vessel permeability to avoid subsequent CW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The influence of sex on the outcome after thrombolysis is a topic of controversy in recent publications. In accordance with our findings, men were approximately 3 times more likely to have good functional outcomes in the GAIN study [4] and Delgato et al [5] identified male sex as a factor for clinical improvement 48 h after intravenous thrombolysis. In contrast, no difference in outcome 90 days after stroke was found in the CASES [6] study in 1,110 thrombolyzed patients and the pooled analysis of the NINDS, ANLANTIS and ECASS (I and II) even showed that women benefited more from rt-PA compared with men [7].…”
Section: Discussionsupporting
confidence: 92%
“…The influence of sex on the outcome after thrombolysis is a topic of controversy in recent publications. In accordance with our findings, men were approximately 3 times more likely to have good functional outcomes in the GAIN study [4] and Delgato et al [5] identified male sex as a factor for clinical improvement 48 h after intravenous thrombolysis. In contrast, no difference in outcome 90 days after stroke was found in the CASES [6] study in 1,110 thrombolyzed patients and the pooled analysis of the NINDS, ANLANTIS and ECASS (I and II) even showed that women benefited more from rt-PA compared with men [7].…”
Section: Discussionsupporting
confidence: 92%
“…Only few of the included studies reported causes other than sICH. Of these, the most frequently cited were malignant oedema, accounting from 14% to 27% of all END 24 causes,23 45 48 52 and early recurrent ischaemic stroke (so-called ERIS35 47), which accounted from 0.6% to 1.8% of all patients with acute strokes in two large studies (228–341 patients),35 47 excluding one potential outlier of 2.9% in a very small study of 34 patients 52. Thus, even after taking into account sICH, malignant oedema and ERIS, a large fraction of END 24 had no reported cause.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary outcome was early neurological deterioration, which was defined as an increase of 4 or more points in the National Institutes of Health Stroke Scale scores from baseline within 7 days after admission, excluding patients who died within 7 days 20, 21…”
Section: Methodsmentioning
confidence: 99%